Working Out the Kinks: Testing the Feasibility of an Electronic Pain Diary for Adolescents with Arthritis - Jennifer N Stinson; Guy C Petroz; Bonnie J Stevens; Brian M Feldman; David Streiner; Patrick J McGrath; Navreet Gill (Pain Research and Management)
BACKGROUND: Current approaches to evaluating pain in children with chronic arthritis suffer from methodological problems. A real-time data capture approach using electronic diaries has been proposed as a new standard for pain measurement. However, there is limited information available regarding the development and feasibility of this approach in children.